2021
DOI: 10.2174/1573396317666210521155111
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Labor Induction and Autism Spectrum Disorders Among Children: A Meta-Analysis

Abstract: Background: There was a hypothesis that the oxytocin used during labor could increase the risk of neurodevelopmental disorders, such as ASD. Objective: This meta-analysis pooled all observational studies to obtain the association between labor induction and the risk of ASD among children. We identified all published studies up to August 2020 through PubMed, Scopus, Web of Science and gray literature. The pooled odds ratios (OR), relative ratio (RR) and 95% confidence intervals (CI (were calculated as random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The study participants did not report or specify the type of used labor-inducing drugs. Recent investigations have indicated a potential correlation between the utilization of drugs during labor and delivery and the emergence of ASD 55 , 56 , especially given the increased usage of epidurals and labor-inducing medications in the past 30 years. However, conflicting findings exist, with some studies suggesting no link between the administration of labor-inducing drugs and the risk of ASD development 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…The study participants did not report or specify the type of used labor-inducing drugs. Recent investigations have indicated a potential correlation between the utilization of drugs during labor and delivery and the emergence of ASD 55 , 56 , especially given the increased usage of epidurals and labor-inducing medications in the past 30 years. However, conflicting findings exist, with some studies suggesting no link between the administration of labor-inducing drugs and the risk of ASD development 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that preterm birth [ 32 ], small for gestational age [ 33 ], prenatal and antenatal depression [ 34 ], and labor induction [ 35 ] are risk factors for ASD, also, some studies have shown that low maternal residential greenness exposure increases the risk of mental disorders such as ASD. The neonatal risk factors such as not breast feeding [ 36 ], low weight, jaundice, congenital heart disease, low birth weight, very low birth weight, and small size for gestational age are increase risk of ASD [ 33 , 37 39 ].…”
Section: Discussionmentioning
confidence: 99%